2011
DOI: 10.3740/mrsk.2011.21.7.384
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Bio-Compatibility of Ti-Nb-Zr-HA Biomaterial Fabricated by Rapid Sintering Using HEMM Powders

Abstract: Ti-6Al-4V ELI (Extra Low Interstitial) alloy has been widely used as an alternative to bone due to its excellent biocompatibility. However, it still has many problems, including a high elastic modulus and toxicity. Therefore, nontoxic biomaterials with a low elastic modulus should be developed. However, the fabrication of a uniform coating is challenging. Moreover, the coating layer on Ti and Ti alloy substrates can be peeled off after implantation. To overcome these problems, it is necessary to produce bulk T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Figure 3 and Table 2 show the microscopic morphology and composition of composite powders after ball milling. It can be found from Figure 3 that the particle size of milled powders is about 5 μm–30 μm compared with the average particle size (about 45 μm) of original powders, which is caused by the continuous cold welding-grinding process during ball milling [ 36 ]. However, research also revealed that refined particles will reunite when the ball milling time is too long [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 and Table 2 show the microscopic morphology and composition of composite powders after ball milling. It can be found from Figure 3 that the particle size of milled powders is about 5 μm–30 μm compared with the average particle size (about 45 μm) of original powders, which is caused by the continuous cold welding-grinding process during ball milling [ 36 ]. However, research also revealed that refined particles will reunite when the ball milling time is too long [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with coating, there are similar complex chemical reactions in uncoated composite. Researchers revealed that some new phases, such as Ca 5 (PO 4 ) 3 (OH), CaTiO 3 , Ti x P y , β-Ti, Ti 2 O, CaO, Ca 4 O(PO 4 ) 2 , Ca 3 (PO 4 ) 2 (TCP), CaTi 4 (PO 4 ) 6 , etc., have appeared in Titanium alloys/HA composites prepared by powder metallurgy and other methods [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. The presence of calcium titanate produced by the reaction between Titanium and HA showed the existence of interfacial chemical reactions [ 27 ].…”
Section: Interfacial Characteristics Of Titanium Alloy/ha Compositmentioning
confidence: 99%
“…Particle shape was also changed from needle-like or disk-like to spherical. Thus, the hardness and corrosion resistance of composites increased with the improvement of milling time due to the grain refinement strengthening effect [ 24 ]. However, the refined particles continued to agglomerate, and the mechanical properties reduced if the ball milling time was too long [ 32 ].…”
Section: Strengthening and Toughening Mechanisms Of Titanium Alloymentioning
confidence: 99%
See 2 more Smart Citations